Bodhi : project journey from a producer’s perspective - Liu, ZhangTeng (2019)
This is a Digita Filmmaking project from the School of Arts, Design and Media. The purpose of the film project is to bring forth the teachings of Buddhism and emphasize on the significance of the religion through engaging narrative and dramatic storytelling.